A Comprehensive Text Book on Self-Emulsifying Drug Delivery Systems. - Kaushik, Deepak; Verma, Ravinder (Singapore : Bentham Science Publishers, 2021)
This text book is a guide for pharmaceutical academics (students and teachers) as well as industry professionals learning about drug delivery and formulation. Chapters presents comprehensive information about self-emulsifying formulations by providing an in-depth understanding of the basic concepts and formulation mechanisms. This information is supplemented by details about current research and development in this field. Readers will learn about the types of self-emulsifying drug delivery systems, evaluation parameters and digestion models, among other topics. Key Features:- 9 chapters organized in a reader-friendly layout- complete guide on self-emulsifying drug delivery formulations, including lipid based systems, SMEDOs, surfactants, and oral dosage forms- includes basic concepts and current developments in research and industrial applications- presents information on conventional and herbal formulations- references for further reading.
SMEDDS AND SNEDDS -- Nano Lipid Carriers (NLCs) -- FORMULATION DEVELOPMENT AND CHARACTERIZATION -- Parameters to be Judged for the Development of the Formulation -- GUIDELINES FOR DESIGNING OF LBFS -- FORMULATION FACTORS INFLUENCING BIOAVAILABILITY OF DRUGS FROM LBDDS -- Lipid Digestion -- Mean Droplet Size of Emulsion -- Hydrophobic Nature of API -- Chemism of Lipids -- Ingredient Selection for LBFs -- ANALYSIS OF EXCIPIENTS IN LBDDS -- Chemical Analysis -- Physical Analysis -- Analysis of Physiological Effects of Ingredients -- MECHANISM OF LIPID-BASED DRUG DELIVERY SYSTEM
Description based upon print version of record.
MECHANISMS FOLLOWED BY LBDDS FOR UPGRADING THE RETENTION.
eBooks on EBSCOhost
Keywords: Excipients; Drug delivery systems; Pharmaceutical Vehicles; Excipients; Drug Delivery Systems; Excipients; Systèmes d'administration de médicaments.; Pharmacology; European; LITERARY COLLECTIONS; MEDICAL; Drug delivery systems; Excipients